A study on voice over LTE (VoLTE) performance and comparison with other voice technology of mobile communications / Akmal Nurhakim Abd Ghani - Abd Ghani, Akmal Nurhakim (2016)
This paper presents the study of Voice over Long Term Evolution (VoLTE) performance and compare against other voice solutions on mobile such as Circuit Switched Fallback (CSFB) and Over-the-Top (OTT). Based on analysis [11], CSFB has many bad results in delivering voice services on LTE mobile network. The ultimate voice solution on LTE networks is VoLTE. TM Berhad joint and Packet One Network are offering VoLTE service soon and their challenge to validate VoLTE performance by using field-trials testing. This paper analyse performance VoLTE by measuring call setup time and media quality of the VoLTE signal. It is performed by taking the measured signals on field trial at Cyberjaya eNodeB with setting LTE FDD 850 MHz band 5. The field trial results which include determining the best measured and VoLTE signal are presented and discussed.